GPS-BASED IONOSPHERE MODELING: A BRIEF REVIEW - Alcay, Salih; Yiğit, Cemal Özer; Seemala, Gopi; Ceylan, Ayhan (Parlar Scientific Publications (P S P), 2014)
Ionosphere modeling has been a highly interesting subject within the scientific community due to its effects on the propagation of electromagnetic waves. Propagation of electromagnetic waves is affected by the electron density in the ionosphere. This electron density is not permanent and it can represent regular and irregular variation according to various factors. Particularly in satellite-based studies (e.g., Positioning with GPS) the structure of the ionosphere must be analyzed well and modeled for removing its effect. Various methods have been proposed for modeling the ionosphere since 1970. In recent years, GPS is used in ionosphere modeling studies extensively. In this paper, the structure of the ionosphere, some developed models and particularly GPS based ionosphere modeling studies are briefly reviewed.
Keywords: Ionosphere modeling; GPS; IRI; Interpolation Techniques; PIM; Solar activity